Potencial uso de Lipase de Fusarium Solani no enriquecimento de ácidos graxos poli – insaturados ômega-3 - SILVA, Allysson Kayron de Carvalho (2023)
Omega-3 is a group of long-chain polyunsaturated fatty oils with multiple double bonds. The main types of omega-3 fatty acids include eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which have several benefits for human health. Techniques exist to fortify these acids, but they result in low concentrations EPA and DHA. Studies show that the use of lipase to enrich EPA and DHA by fish oil is very promising due to its low cost compared to other techniques already used. For this reason, the aim of this study was to verify the potential use of Fusarium solani from the fungus collection of the Federal University as a source of lipase production and the use of this enzyme in the enrichment of omega-3 polyunsaturated acids 3 EPA and DHA. The enzymatic index was compared with Aspergillus niger, Aspergillus flavus, Curvularia sp., Fusarium oxysporum and Penicillium decumbens, the type of fermentation, partial purification, physicochemical characterization and the ability to enrich EPA and DHA. The obtained results show that Lipase F2 has a lipolytic activity of 290 U/mL at pH 8.0 and a stability of 93.84 U/mL in the same pH range, shows resistance at temperatures from 35 to 70°C, stability at temperatures up to 35°C and different types of surfactants and ions. Lipase F2 was obtained by improving submerged fermentation for lipase production using 5% (v/v) coconut oil for 3 days of lipase production, lipase F2 showed the ability to obtain EPA and DHA by fish oil, where the results were 22.1 mol% of DHA and 23.8 mol% of EPA, showing that this enzyme obtained from Fusarium solani has catalytic properties.